Outcomes of RigidFix Cross Pin Fixation in Femoral and Tibial Tunnel for Anterior Cruciate Ligament Reconstruction - Wei Yuan; Wei Qi; Tingting Hu; Jia Zhang; Ming‐yang An; Gang Zhao; Xiao‐ping Wang; Chunbao Li; Yujie Liu (Orthopaedic Surgery, 2024)
Objectives There is no clear consensus so far on which fixation method is most favorable for the tibial tunnel in anterior cruciate ligament reconstruction (ACLR). The purpose of this paper is to investigate the outcome of RigidFix cross pins fixation in the tibial tunnel and to explore the advantages of RigidFix applied both in the femoral and tibial tunnel with hamstring tendon graft in anterior cruciate ligament reconstruction. Methods This retrospective study included 53 patients (male/female, 45/8) who underwent anterior cruciate ligament reconstruction using autologous hamstring tendons between January 2013 and December 2017 at our institute. The participants in group A (n = 36) received anterior cruciate ligament reconstruction with RigidFix cross pins fixation in both femoral and tibial tunnels, while those in group B (n = 17) with RigidFix cross pins fixation in the femoral tunnel and Interference screw fixation in the tibial tunnel. The visual analogue scale (VAS) score, International Knee Documentation Committee subjective knee form 2000 (IKDC2000) score, Lysholm knee scoring scale, Tegner activity score and the side‐to‐side difference were compared at 2 and 5 years postoperatively. The graft diameter, number of strands in graft and the average diameter of each strand were also compared between the two groups. The categorical parameters were analyzed by chi‐square test and the continuous variables conforming to a normal distribution were analyzed by Student's t‐test. Results At 2 years postoperation, the VAS score (1.61 ± 0.55), side‐to‐side difference (1.50 ± 0.58) in group A were significantly lower than that in group B, and the IKDC2000 score (88.81 ± 3.88), Tegner activity score (6.14 ± 0.60) in group A were significantly higher than that in group B. At 5 years postoperation, the VAS score (1.64 ± 0.68), side‐to‐side difference (1.73 ± 0.63) in group A were significantly lower than that in group B, and the IKDC2000 score (89.09 ± 3.85), Tegner activity score (6.58 ± 0.94) in group A were slso significantly higher than that in group B. There was statistical difference in the change of the side‐to‐side difference between the two groups (group A vs. B, 0.22 ± 0.08 vs. 0.34 ± 0.11, p < 0.001). There were also statistical differences in the graft diameter (group A vs. B, 7.83 ± 0.74 vs. 7.41 ± 0.51, p = 0,038), number of strands in graft (5.67 ± 0.72 vs. 4.00 ± 0.00, p < 0.001) and the average diameter of each strand (1.41 ± 0.22 vs. 1.85 ± 0.13, p < 0.001) between the two groups. Conclusion RigidFix cross pins fixation in the tibial tunnel for anterior cruciate ligament reconstruction can achieve better 5‐year results when compared with the interference screw, and the hamstring tendon can be folded into a thicker graft when RigidFix cross pins were applied in both femoral and tibial tunnels.